Research Output of Nanorobot with Special Reference to Scopus Database: Scientometric Analysis - Prakash, M.; Arumugam, J.A.; Janen, T. (University of Kelaniya, Sri Lanka., 2023)
The analysis reveals interesting patterns in research productivity and citation activity over time. The year 2020 stands out as the period with the highest research output, while the early years had limited publication and citation activity. The findings also highlight influential authors in the field, such as Sitti M and Li Y, who have made significant contributions and achieved high H- indices and citation counts. The study further examines the publication types and sources that contribute to nanorobot research, emphasizing the predominance of articles and the impact of journals such as IEEE Robotics and Automation Letters. The analysis also sheds light on global collaboration, with China and the United States leading in terms of research output, followed by countries like India, Japan, and Iran. Moreover, the study identifies highly cited papers that have played a pivotal role in shaping the field of nanorobotics. These findings provide valuable insights into the research landscape of nanorobotics, including trends in research output, influential authors and sources, and global collaborations. The analysis contributes to the understanding of the field's development, impact, and knowledge diffusion, offering a comprehensive overview of the research output in nanorobotics. Researchers, scholars, and practitioners interested in nanorobotics will benefit from the identified influential papers and the understanding of key contributors and research trends. This scientometric analysis serves as a valuable resource for further exploration, advancement, and interdisciplinary collaborations in the field of nanorobotics.
Keywords: Nanorobot; Research Output; Scopus Database; Robotics; Scientometrics